Clinical characteristics and overall survival prognostic nomogram for metaplastic breast cancer - Zheng, Caihong; Fu, Chengbin; Wen, Yahui; Liu, Jiameng; Lin, Shunguo; Han, Hui; Han, Zhonghua; Xu, Chunsen (Frontiers in Oncology, 2023)
Background: Metaplastic breast cancer (MBC) is a rare breast tumor and the prognostic factors for survival in patients still remain controversial. This study aims to develop and validate a nomogram to predict the overall survival (OS) of patients with MBC. Methods: We searched the Surveillance, Epidemiology, and End Results (SEER) database for data about patients including metaplastic breast cancer and infiltrating ductal carcinoma (IDC) from 2010 to 2018. The survival outcomes of patients between MBC and IDC were analyzed and compared with the Kaplan-Meier (KM) method. MBC patients were randomly allocated to the training set and validation Ⅰ set by a ratio of eight to two. Meanwhile, the performance of this model was validated again by the validation Ⅱ set, which consisted of MBC patients from the Union Hospital of Fujian Medical University between 2010 and 2018. The independent prognostic factors were selected by univariate and multivariate Cox regression analyses. The nomogram was constructed to predict individual survival outcomes for MBC patients. The discriminative power, calibration, and clinical effectiveness of the nomogram were evaluated by the concordance index (C-index), the receiver operating characteristic (ROC) curve, and the decision curve analysis (DCA). Results: MBC had a significantly higher T stage (T2 and above accounting for 75.1% vs 39.9%), fewer infiltrated lymph nodes (N0 accounted for 76.2% vs 67.7%), a lower proportion of ER, PR, and HER-2 positive, radiotherapy but more chemotherapy, and a higher rate of mastectomy, which was discovered when comparing the clinical baseline data between MBC and IDC. Age at diagnosis, T, N, and M stage, as well as surgery and radiation treatment, were all significant independent prognostic factors for overall survival (OS). In the validation Ⅰ cohort, the nomogram's C-index (0.769) was indicated to be considerably higher than the standard AJCC model's (0.700). Nomogram's great predictive capability capacity further was supported by the comparatively high C-index of the validation II sets (0.728). Conclusions: Metaplastic breast cancer is more aggressive, with a worse clinical prognosis than IDC. This nomogram is recommended for patients with MBC, both American and Chinese, which can help clinicians make more accurate individualized survival analyses.